Different Antigen-Specific CD4+ and CD8+ T-Cell Response against HCMV Proteins in Pregnant Women with Primary Infection and in Control Subjects with Remote Infection - Zavaglio, Federica; d’Angelo, Piera; Fornara, Chiara; Zelini, Paola; Comolli, Giuditta; Furione, Milena; Arossa, Alessia; Spinillo, Arsenio; Lilleri, Daniele; Baldanti, Fausto (Journal of clinical medicine, 2024)
Background/Objectives: Human cytomegalovirus (HCMV) is the most frequent cause of congenital infections. The HCMV-specific T-cell response in primary infection may help define reliable correlates of immune protection in pregnancy. In this study, the antigen-specific T-cell response against different HCMV proteins (IE-1, pp65, gB, gHgLpUL128L) was investigated in pregnant women with primary infection and in control subjects with remote infection to identify possible components of a vaccine. Methods: Blood samples from 35 pregnant women with HCMV primary infection and 30 HCMV-seropositive healthy adult subjects with remote infection were tested. The antigen-specific T-cell response was measured using cytokine intracellular staining after stimulation with IE-1, pp65, gB and gHgLpUL128L peptides pool. Results: The pp65-specific CD4+ T-cell response was higher in pregnant women with HCMV primary infection at the late time point and in control subjects with remote infection, while the pregnant women at the early time point showed a higher gB-specific CD8+ T-cell response. Regarding the CD4+ and CD8+ T-cell phenotypes, we observed that HCMV-specific CD4+ and CD8+ T cells expressing CD45RA+ remained constant in pregnant women with primary infection at the early and late time points and in subjects with remote infection, while HCMV-specific CD4+ and CD8+ T cells expressing IL-7R+ or producing IL-2 were higher in control subjects with remote infection than in pregnant women with HCMV primary infection. Conclusions: The T-cell response was higher against gB in the early phase of infection and against pp65 in the late phase. Therefore, these proteins should be taken into consideration as candidates for a vaccine.